2005
DOI: 10.1111/j.1365-2052.2005.01253.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase mutations associated with Siamese and Burmese patterns in the domestic cat (Felis catus)

Abstract: The Siamese cat has a highly recognized coat colour phenotype that expresses pigment at the extremities of the body, such as the ears, tail and paws. This temperature-sensitive colouration causes a 'mask' on the face and the phenotype is commonly referred to as 'pointed'. Burmese is an allelic variant that is less temperature-sensitive, producing more pigment throughout the torso than Siamese. Tyrosinase (TYR) mutations have been suspected to cause these phenotypes because mutations in TYR are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 26 publications
4
81
0
2
Order By: Relevance
“…These types of observations, first made by Sewall Wright (1917c) and later by Clarence Cook Little (1957) and A. G. Searle (1968), foreshadowed the field of comparative genomics. Indeed, comparison of genome sequences not only clarified the evolutionary relationships among mammals (and most other organisms), but also provided the tools to identify molecular alterations responsible for the Tyrosinase color series in mice (Kwon et al 1989), cats (Lyons et al 2005;Schmidt-Kuntzel et al 2005), cattle (Schmutz et al 2004), and rabbits (Aigner et al 2000) (although, ironically, not yet in guinea pigs).…”
Section: Discussionmentioning
confidence: 99%
“…These types of observations, first made by Sewall Wright (1917c) and later by Clarence Cook Little (1957) and A. G. Searle (1968), foreshadowed the field of comparative genomics. Indeed, comparison of genome sequences not only clarified the evolutionary relationships among mammals (and most other organisms), but also provided the tools to identify molecular alterations responsible for the Tyrosinase color series in mice (Kwon et al 1989), cats (Lyons et al 2005;Schmidt-Kuntzel et al 2005), cattle (Schmutz et al 2004), and rabbits (Aigner et al 2000) (although, ironically, not yet in guinea pigs).…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression studies have shown that the 402Q variant encodes a thermolabile enzyme [40] , and in primary melanocyte cultures we have shown that it is retained in the endoplasmic reticulum, hypoglycosylated and preferentially degraded [45] . Interestingly, thermolabile TYR alleles are the basis of the Siamese/Burmese cat coat colours, where pigment appears darkest at the extremities of the body [46] ; this condition is also present in some human albino patients as subtype OCA1B [39] . Recent studies have shown that the TYR genotype is likely to be a significant modifier of other pigmentation gene polymorphisms in human skin, hair and eye colour, and associated with naevus count, though not apparent by body site there is potential for thermal changes in pigmentation of the skin and hair [45] .…”
Section: Tyr (Oca1)mentioning
confidence: 99%
“…b sont qualifiés de mink et présentent un contraste moyen entre les extrémités et le reste du corps. Leurs yeux sont couleur « aiguemarine » (figure 9) (Lyons et al 2005). …”
Section: Shadedunclassified